The curious case of innovative minds: An analysis of the world's most creative people's discourse / Nadhratunnaim Abas and Harlina Yunus @Junor - Abas, Nadhratunnaim; Yunus @Junor, Harlina (2010)
Novelty is the bread and butter of creativity and innovation. In order to embrace novelty in the classroom, the seeds of curiosity through the promotion of inquisitive thinking should be cultivated. Previous studies that experiment the incorporation of inquisitive thinking in the classroom indicate that it has made the learning more meaningful and valuable to students. The present study seeks to investigate the significance of inquisitive thinking in its role to promote creativity and innovation by analysing the discourse of the five randomly selected most creative people in the world as listed by an online business magazine, FastCompany.com. The findings have verified the importance of the inquisitive thinking represented through the formation of interrogatives or questions in everyone minute of each of the five speeches. This has evidently highlighted the importance of inquisitive thinking in the paths of creativity and innovation.